Fecal Microbial Signatures Are Associated With Engraftment Failure Following Umbilical Cord Blood Transplantation in Pediatric Crohn’s Disease Patients With IL10RA Deficiency - Xue, Aijuan; Qian, Xiaowen; Gao, Xuefeng; Wang, Ping; Wang, Lin; Zheng, Cuifang; Huang, Zhiheng; Hu, Wenhui; Shi, Jieru; Huang, Ying (Frontiers in Pharmacology, 2020)
Objectives: Umbilical cord blood transplantation (UCBT) is associated with a relatively high rate of engraftment failure. This study aimed at exploring whether any fecal microbiota could be associated with engraftment failure following UCBT in Crohn’s disease patients with IL10RA deficiency. Methods: Thirteen patients were recruited and their 230 fecal samples were collected longitudinally from immediately before conditioning chemotherapy to 8 weeks post the UCBT. The V3-V4 regions of the bacterial 16S rRNA gene were amplified by PCR and sequenced, followed by bioinformatics analyses. Results: Following the UCBT, 7 out of 13 patients achieved neutrophil and platelet engraftment with a median of 21 and 28 days, respectively (S group), while 6 patients failed to achieve engraftment (F group). In comparison with that in the S group, significantly lower Shannon diversity values on the UCBT day (P=0.0176) and less abundance of Bifidobacterium longum, Bifidobacterium pseudolongum, Enterobacteriaceae_538000, and one taxon of Lachnospiraceae family was detected in the F group, accompanied by significantly higher abundances of four taxa including Lautropia, Pseudomonas, and species Microvirgula aerodenitrificans during the chemotherapy period as well as UCBT. The abundances of thirty OTUs were correlated significantly with clinical indices. Conclusions: Microbial indicators of reduced diversity of microbiota and signatures of specific bacterial abundances, such as a lower abundance of Bifidobacterium longum, for engraftment failure would require validation. These indicators may help for the risk stratification in patients with IL10RA deficiency undergoing UCBT.